Chapter Forme e funzioni della documentazione contabile nelle signorie rurali italiane (secolo XIII-inizio secolo XV): appunti per un questionario - Buffo, Paolo (Reti Medievali E-Book, 2023)
The essay aims to develop a questionnaire for the study of the accounting records of late medieval rural lordships, combining the problems and methods of medievalist historiography and diplomatics. Firstly, the textual types and functions of accounting records are analysed, dividing them into income lists and officers' accounts and observing their evolution in the light of the general transformations of documentary writing during the late Middle Ages. A detailed analysis of the parallels between seigniorial accounts and the accounts of the central powers is then carried out, with particular attention to north-western Italy.